“Don’t marry, be happy!” – how single women in Malaysia view marriage - Azmawati, Azman Azwan; Mohd Hashim, Intan Hashimah; Endut, Noraida (EDP Sciences, 2015)
The aim of this study is to explore how single women in Malaysia who have never been married view marriage and related issues. Two-hundred single women between the ages of 24 to 66 were interviewed in this study. Participants reported their view on gender and marriage (42-items), social expectations related to their marital status (12-item) and their marital plan. Participants reported moderately traditional view about gender and marriage experienced some level of expectations to get married and although they generally felt positive with their current status of being single, they were still open to the idea of marriage. Ideal characteristics of a partner include kindness, sincerity, responsibility and maturity. Findings indicated realistic but open expectations related to marriage.